Sperm sequencing reveals extensive positive selection in the male germline - Matthew D. C. Neville; Andrew R. J. Lawson; Rashesh Sanghvi; Federico Abascal; My H. Pham; Alex Cagan; Pantelis A. Nicola; Tetyana Bayzetinova; Adrian Baez-Ortega; Kirsty Roberts; Stefanie V. Lensing; Sara Widaa; et al. (Nature, 2025)
Abstract Mutations that occur in the cell lineages of sperm or eggs can be transmitted to offspring. In humans, positive selection of driver mutations during spermatogenesis can increase the birth prevalence of certain developmental disorders 1–3 . Until recently, characterizing the extent of this selection in sperm has been limited by the error rates of sequencing technologies. Here we used the duplex sequencing method NanoSeq 4 to sequence 81 bulk sperm samples from individuals aged 24–75 years. Our findings revealed a linear accumulation of 1.67 (95% confidence interval of 1.41–1.92) mutations per year per haploid genome driven by two mutational signatures associated with human ageing. Deep targeted and exome NanoSeq 5 of sperm samples identified more than 35,000 germline coding mutations. We detected 40 genes (31 newly identified) under significant positive selection in the male germline that have activating or loss-of-function mechanisms and are involved in diverse cellular pathways. Most of the positively selected genes are associated with developmental or cancer predisposition disorders in children, whereas four of the genes exhibited increased frequencies of protein-truncating variants in healthy populations. We show that positive selection during spermatogenesis drives a 2–3-fold increased risk of known disease-causing mutations, which results in 3–5% of sperm from middle-aged to older individuals with a pathogenic mutation across the exome. These findings shed light on germline selection dynamics and highlight a broader increased disease risk for children born to fathers of advanced age than previously appreciated.